The Effect of Fundamental Ratios on Stock Returns In The Coal Mining Sector on The Idx (2018-2023) - Mudzakir Mudzakir; Temy Setiawan (Publikasi Indonesia, 2024)
This research aims to examine the impact of financial ratios, including Debt to Equity Ratio (DER), Current Ratio (CR), and Accounts Receivables Turnover Ratio (RTO), on Stock Return, mediated by Return on Equity (ROE). The background of this study highlights the role of various financial ratios, such as solvency ratio (DER), liquidity ratio (CR), activity ratio (RTO), and profitability ratio (ROE), on stock returns. Previous research has shown varied results regarding the influence of financial ratios on stock returns. This research employs a quantitative descriptive method with Stata as the analytical tool. It eval_uates the impact of DER, CR, RTO, ROE, and Stock Return on coal mining companies listed on the Indonesia Stock Exchange (IDX) during the period of 2018-2023. The total sample comprises 108 data points from 18 companies. The analytical method used is multiple linear regression with panel data, processed using Stata. The results indicate that DER, CR, and RTO do not affect stock returns, whereas ROE significantly affects stock returns. DER affects ROE, while CR and RTO do not affect ROE. Additionally, ROE as an intervening variable does not mediate the influence of DER, CR, and RTO on stock returns. This research is expected to assist investors in analyzing the stocks of coal mining companies traded on the Indonesia Stock Exchange and help companies optimize their financial performance, enhance operational performance, and ultimately maximize shareholder value.